2009
DOI: 10.1161/circulationaha.108.806505
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Trial of Doxycycline for Matrix Metalloproteinase-9 Inhibition in Patients With an Abdominal Aneurysm

Abstract: Background-Doxycycline has been shown to effectively inhibit aneurysm formation in animal models of abdominal aortic aneurysm. Although this effect is ascribed to matrix metalloproteinase-9 inhibition, such an effect is unclear in human studies. We reevaluated the effect of doxycycline on aortic wall protease content in a clinical trial and found that doxycycline selectively reduces neutrophil-derived proteases. We thus hypothesized that doxycycline acts through an effect on vascular inflammation. Methods and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
205
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(210 citation statements)
references
References 39 publications
(55 reference statements)
3
205
1
1
Order By: Relevance
“…MMP-9 is considered one of the pharmacological targets in the treatment of glaucoma [15] and other diseases [19][20][21][22]. Thus, the knowledge of the mechanisms regulating MMP-9 is important for the understanding of the neuron survivaldeath pathways and for deciphering the glaucomatous alterations in the retina and optic nerve.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-9 is considered one of the pharmacological targets in the treatment of glaucoma [15] and other diseases [19][20][21][22]. Thus, the knowledge of the mechanisms regulating MMP-9 is important for the understanding of the neuron survivaldeath pathways and for deciphering the glaucomatous alterations in the retina and optic nerve.…”
Section: Introductionmentioning
confidence: 99%
“…In two previous studies, we have shown that brief 2-4-week pre-operative interventions with doxycycline and the ACE inhibitor ramipril profoundly reduced aortic wall inflammation through, respectively, the effects on the AP-1 (doxycycline) 26 and NFκB 27 proinflammatory pathways. Similarly, it was found that statins dose dependently reduce NFκB-driven inflammation in the aneurysm wall.…”
Section: Discussionmentioning
confidence: 92%
“…Yet, if such effects exist, they presumably compare weakly with the effect exerted on the NFAT pathways, and with pleiotropic effects on NFκB and AP-1 signaling exerted by, respectively, statins 28 and ACE inhibitors, 27 and doxycycline. 26 A further limitation of the study is that evaluation of baseline vitamin D status was not included in the study protocol. We therefore assessed vitamin D levels in plasma from AAA patients participating PHAST study who were included in same center as the patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this compound enhances Cystatin C and TIMP-1, important MMP inhibitors [81]. Beyond regulating the major extracellular matrix modulators, doxycycline also produced a significant and selective suppression of aortic wall inflammation by reducing neutrophil infiltration, as well as cytotoxic T-cell and vascular cytokines [82].…”
Section: Tetracyclinementioning
confidence: 99%